Predicting debt burden status among Malaysia civil servants - Sabri, Mohamad Fazli; Abdullah, Nuraini; Abdul Rahim, Husniyah; Yusof, Radduan; Othman, Mohd. Amim; Hashim, Ahmad Hariza (UiTM Press, 2019)
The pressure of high inflation rate and increased cost of living has invoked the concerns over the problem of debt among civil servants in Malaysia. This paper aims to investigate the determinants of debt burden status within a civil servants’ sample. Questionnaires were distributed using a multi-stage random sampling method. A total of 600 responses were collected. Results from logistic regression showed several significant predictors of debt burden status, namely savings to income ratio, financial status, and income adequacy. This study outlined the predictors of debt burden status among Malaysian civil servants, providing civil servants with some ideas to counter debt issues which have been prevalent for a long time.